2013
DOI: 10.1016/j.neuroscience.2013.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP stimulates neurite outgrowth of lamprey reticulospinal neurons without substantially altering their biophysical properties

Abstract: Reticulospinal (RS) neurons are critical for initiation of locomotor behavior, and following spinal cord injury (SCI) in the lamprey, the axons of these neurons regenerate and restore locomotor behavior within a few weeks. For lamprey RS neurons in culture, experimental induction of calcium influx, either in the growth cone or cell body, is inhibitory for neurite outgrowth. Following SCI, these neurons partially downregulate calcium channel expression, which would be expected to reduce calcium influx and possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
0
14
1
Order By: Relevance
“…In vitro, a cAMP analog promotes an increase in the distance axons regenerate [312,313]. In vivo, the elevation of cAMP in axotomized neurons accelerates peripheral axon outgrowth by increasing the levels of neuron-produced endogenous neurotrophic factors [314].…”
Section: Platelet-released Factorsmentioning
confidence: 99%
“…In vitro, a cAMP analog promotes an increase in the distance axons regenerate [312,313]. In vivo, the elevation of cAMP in axotomized neurons accelerates peripheral axon outgrowth by increasing the levels of neuron-produced endogenous neurotrophic factors [314].…”
Section: Platelet-released Factorsmentioning
confidence: 99%
“…). Although it cannot be excluded that changes in cAMP levels during regeneration may contribute to the increased GH (Lau et al ., ; Pale et al ., ), the simplest explanation for the increased GH remains the increased electrical access to the internode, as it was the case with GKfN. This is supported by the fact that GH showed a marked recovery with regeneration from 1 to 5 months, in parallel with recovery in passive GBB linking the nodal and internodal compartments (Barrett & Barrett, ; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a single dose of cAMP applied at the time of transection promotes axon regeneration of identifiable descending neurons following a complete spinal cord transection in larval sea lampreys [23][24][25] . Here, and to reveal a possible involvement of this second messenger in the inhibitory effect of serotonin in axonal regeneration, we carried out a rescue experiment in which animals treated with 6 serotonin as above were also treated with dibutyryl-cAMP (db-cAMP).…”
Section: Camp Treatment Can Reverse the Inhibitory Effect Of Serotonimentioning
confidence: 98%
“…Several reports in mammals and fishes have shown that cAMP promotes axon regeneration following SCI [18][19][20][21][22] . Subsequent studies have also shown that cAMP promotes axon regeneration in descending neurons of lampreys after SCI [23][24][25] . The challenge now is to define the signals that control cAMP levels in descending neurons after axotomy and during regeneration.…”
Section: Introductionmentioning
confidence: 94%